2016
DOI: 10.1111/iep.12184
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy with metformin and insulin attenuates systemic and hepatic alterations in a model of high‐fat diet‐/streptozotocin‐induced diabetes

Abstract: In this study we have explored the pathogenesis of the hepatic alterations which occur in diabetes and the modulation of these complications by the combination of metformin adjunct treatment and insulin monotherapy. For this purpose, diabetic rats were treated with insulin (DM + Ins) or metformin plus insulin (DM + Met + Ins). Biochemical and cardiometabolic parameters were analysed by spectrophotometry. Intravital microscopy was used to study the hepatic microcirculation. In the liver tissue, real-time PCR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 92 publications
(161 reference statements)
2
20
0
Order By: Relevance
“…; Silvares et al . ) were reported by several investigators. Also in the current study, HFD+STZ treatment of rats resulted in hyperglycaemia, dyslipidaemia and hepatic steatosis and inflammation as assessed through biochemical and histopathologic findings.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…; Silvares et al . ) were reported by several investigators. Also in the current study, HFD+STZ treatment of rats resulted in hyperglycaemia, dyslipidaemia and hepatic steatosis and inflammation as assessed through biochemical and histopathologic findings.…”
Section: Discussionmentioning
confidence: 94%
“…; Silvares et al . ). In this study, although no significant changes were detected in body weight due to HFD+STZ treatment, HFD+STZ rats showed a tendency to decrease body weight.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Silvares et al have shown an elevated oxidative stress with inflammation, microvascular damage and AGEs deposition in HFD-/STZ-induced diabetes in rats [11]. Hyperglycemia induces ROS production, that initiate a chain reaction leading to an increased inflammatory response and chemical modification of lipoproteins [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, this type of carbohydrate was not used, since this would not allow knowing if the manifestation of the complications and comorbidities would be exclusively due to the increase of the amount of fat or its association with a carbohydrate with harmful capacity. It is believed that other factors may also have influenced this result as time of exposure to diet, fat percentage, and type (saturated or unsaturated) and source (animal or vegetable) of fatty acids and animal model [6,17,18,30,33,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%